Phone Skills for the Information Age - Maxwell Dorothy (Mc Graw Hill, 2005)
This five-hour program teaches proper phone use to help students develop and maintain professional relationships, project a positive company image, and provide reliable service. Phone Skills for the Information Age features realistic situations and problems found in today's increasingly complex business environments. The text includes reinforce